Peramalan Nilai Rugi Daya Pada Serat Optik Glass Akibat Pengaruh Tekanan dan Suhu Berbasis Interpolasi Lagrange - Tamimah, Ni’matut; Chitami Priawan Siregar, Aslam (Jurnal Jaring SainTek, 2023)
A study has been carried out using SMS structured glass optical fiber (Singlemode-Multimode-Singlemode) as a pressure and temperature sensor to detect cracks in the highway structure. In that research, the methods used are experimental and simulation methods. The experimental method uses OTDR (Optical Time Domain Reflectometer), but the simulation method uses Lagrange interpolation. Next, two kinds of SMS structured glass optical fiber are used the multimode length of 6.5 cm and 7 cm at temperatures 470C dan 570C. Based on the experimental results, the SMS structured glass optical fiber with a multimode length of 7 cm has a better level of linearity than a multimode length of 6.5 cm, equal to 94.83% for 470C and 86,45% for 570C. As for the error of the power loss value that occurs, based on the experimental results on the simulation results for a multimode length of 7 cm on a glass fiber optic sensor with an SMS structure, it has an error smaller than a multimode length of 6.5 cm, which is 1.301% when it is measured on 570C. Therefore, the SMS structured glass optical fiber with a multimode length of 7 cm is more suitable for use as a pressure sensor.